1991
DOI: 10.1128/cmr.4.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii, an opportunist in immunocompromised patients

Abstract: Pneumocystis carinii has been recognized as a cause of pneumonia in immunocompromised patients for over 40 years. Until the 1980s, Pneumocystis pneumonia (pneumocystosis) was most often seen in patients undergoing chemotherapy for malignancy or transplantation. Infection could be prevented by trimethoprim-sulfamethoxazole prophylaxis; thus, it was an uncommon clinical problem. With the onset of the AIDS epidemic, Pneumocystis pneumonia has become a major problem in the United States because it develops in appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
0
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 157 publications
0
38
0
5
Order By: Relevance
“…In the absence of specific antimicrobial prophylaxis, Pneumocystis carinii causes pneumonia in the majority of individuals infected with human immunodeficiency virus and remains an important pathogen in persons treated with immunosuppressive therapy for malignancy and after organ transplantation (6). The toxicity and the incomplete efficacy of the standard treatment regimens for P. carinii pneumonia have prompted the development of new or adjunctive modes of therapy (6,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of specific antimicrobial prophylaxis, Pneumocystis carinii causes pneumonia in the majority of individuals infected with human immunodeficiency virus and remains an important pathogen in persons treated with immunosuppressive therapy for malignancy and after organ transplantation (6). The toxicity and the incomplete efficacy of the standard treatment regimens for P. carinii pneumonia have prompted the development of new or adjunctive modes of therapy (6,27).…”
mentioning
confidence: 99%
“…The toxicity and the incomplete efficacy of the standard treatment regimens for P. carinii pneumonia have prompted the development of new or adjunctive modes of therapy (6,27).…”
mentioning
confidence: 99%
“…1) is an inhibitor of ⌬ 24(25) -sterol methyltransferase (24-SMT) in fungal cells (2) and in both epimastigotes and amastigotes of the protozoan parasite Trypanosoma cruzi (23,52,53); it has also been shown that this compound is a potent antiproliferative agent against this parasite both in vitro and in vivo (52,53). Pneumocystis carinii, an opportunistic fungal pathogen which, in contrast to other fungi, is completely resistant to azoles and ampthotericin B (3,4,13,27,45), is also susceptible to 22,26-azasterol in vitro (55).…”
mentioning
confidence: 99%
“…Though apparently less severe in patients with other immune disorders (22), these infections can nonetheless cause major clinical problems during immunosuppressive cancer chemotherapy or when immunosuppressant drugs are administered as part of a bone marrow transplantation program (4,33). Several classes of compounds have found use in the treatment and/or prophylaxis of P. carinii and T. gondii infections, but none to date has been entirely successful.…”
mentioning
confidence: 99%